Searching for Own Space: Korean Female Graduate Students’ (Re)construction of Their Professional Selves in the U.S. Academia - Heh Youn Shin; Hyewon Park (Adult Education Research Conference, 2018)
Taking the transnational feminist approach, the purpose of this study is to investigate the perceptions and experiences of Korean female graduate students in the U.S. higher education institution and the host society.
Keywords: female international students; transnational feminism; higher education; identity development